Analisis Proses Pembelajaran Daring di Masa Pandemi Covid-19 Pada Siswa Kelas V SDN 2 Wulung Blora - Siti Febriliana Nur Avivah; M. Yusuf Setia Wardana; Husni Wakhyudin (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The Covid-19 pandemic has made the education system a bit of a bottleneck. Almost all regions implement online learning systems. This study discusses the implementation of online learning with the aim of knowing the online learning system for fifth grade students, knowing the implementation of online learning for fifth grade students, and evaluating the implementation of online learning for fifth grade students. In this study, the authors used qualitative research methods with data collection techniques using observation, interviews, questionnaires, and documentation. The subjects of this research are the principal, fifth grade homeroom, and fifth grade students. Research is carried out directly at school and online. The results of this study include: 1) the implementation online learning has been carried out since the beginning of the covid-19 pandemic or in March 2020, 2) online learning evaluation is carried out by the teacher to find out the obstacles that occur during online learning, and 3) the response of teachers and students during online learning is that the teacher has difficulty delivering material while students also find it difficult to receive material explanations.